Fiona the fruit bat - Riskin, Dan (Greystone Kids, 2022)
"A sweet, fun, and informative picture book about bat echolocation for kids 3-7. Written by a scientist who works with bats in his everyday life! It's time for Fiona the fruit bat to take her very first flight, but she's scared. How will she fly when she can't see in the dark? Mama just says, "listen." But how will listening help her to see? Then she hears a mysterious sound from deep in her cave. To find out what's making that noise--and to finally fly--Fiona will have to unlock a secret hidden inside herself. Written by biologist and bestselling author Dan Riskin, and rooted in the real-life biology of short-tailed fruit bats, this adorable story features: The fascinating science behind echolocation, including backmatter pages with information on fruit bats from the author. A comforting message to help kids scared of the dark: Alongside Fiona, they'll learn there's nothing to be scared of! A celebration of self-confidence and independence: Shows readers the amazing things they can accomplish all on their own. Accompanied by delightful illustrations from Rachel Qiuqi, Fiona the Fruit Bat is a touching tale about overcoming the fear of new experiences and finding the courage to listen to your own voice."--